The Effect of The Proactive Guide Strategy on The Achievement of Second Grade Middle School Students In The Subject of Dictation (Journal of the College of Basic Education, 2025)
Abstract: This research was conducted with the aim of identifying the effect of the proactive guide strategy on the achievement of second grade students in the average subject of dictation. In order to achieve the aim of the research, the researcher formulated a null hypothesis, which is: There is no statistically significant difference at the significance level (0.05) between the average scores of students in the experimental group who master dictation using the proactive guide strategy and the average scores of students in the control group who master the same subject using the categorical method in the post-test prepared by the researcher. The researcher adopted the design The experimental study was conducted with partial control of the two research groups. Two members (the experimental and the control) were subjected to the post-test. The middle schools in Diyala Governorate were chosen to be the research community. The research sample was 68 students, 34 in the experimental courses and 34 in the control group. It was concluded that the experimental group outperformed the control group in the achievement of the material.